Thomas Aquinas : a portrait - Turner, Denys, 1942- (Yale University Press, 2013)
Leaving so few traces of himself behind, Thomas Aquinas seems to defy the efforts of the biographer. Highly visible as a public teacher, preacher, and theologian, he nevertheless has remained nearly invisible as man and saint. What can be discovered about Thomas Aquinas as a whole? In this short, compelling portrait, Denys Turner clears away the haze of time and brings Thomas vividly to life for contemporary readers-those unfamiliar with the saint as well as those well acquainted with his teachings. Building on the best biographical scholarship available today and reading the works of Thomas with piercing acuity, Turner seeks the point at which the man, the mind, and the soul of Thomas Aquinas intersect. Reflecting upon Thomas, a man of Christian Trinitarian faith yet one whose thought is grounded firmly in the body's interaction with the material world, a thinker at once confident in the powers of human reason and a man of prayer, Turner provides a more detailed human portrait than ever before of one of the most influential philosophers and theologians in all of Western thought.